THE INKLUSIRKULAR MODEL FOR INCLUSIVE GREEN ECONOMIC WELL BEING - Didik Gunawan; Willy Cahyadi; Imelda Mardayanti (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Indonesia faces an escalating waste management crisis, with national waste generation reaching 35–38 million tons annually and only 32–40% managed formally. The 2025 North Sumatra flash floods, which claimed over 1,100 lives, highlighted how uncontrolled waste accumulation in drainage systems exacerbates hydrometeorological disasters. In medium-sized cities like Tebing Tinggi, where daily waste generation reaches 120–150 tons and landfill capacity is overloaded, the informal sector—comprising waste pickers and small-scale recyclers—plays a critical yet marginalized role in material recovery. This study aims to design, develop, and validate the INKLUSIRKULAR Model, an inclusive circular economy framework that bridges formal and informal sectors to reduce unmanaged waste, mitigate flood risks, and enhance inclusive green economic well-being. Using a convergent parallel mixed-method design, the study combines Structural Equation Modeling-Partial Least Squares (SEM-PLS) with 250 respondents and Participatory Action Research (PAR) involving 20 key informants, including waste pickers, environmental agencies, MSMEs, and flood-affected communities. The SEM-PLS results reveal that economic feasibility (β = 0.318), environmental sustainability (β = 0.306), and social justice (β = 0.294) are the strongest direct predictors of inclusive green economic well-being, explaining 63.5% of variance (R² = 0.635). Partial mediation analysis confirms that community economic empowerment mediates the effects of environmental sustainability and social justice, while waste-based innovation mediates economic feasibility and environmental sustainability. However, economic feasibility does not significantly empower communities collectively, indicating that institutional interventions are required beyond individual income gains. The PAR findings demonstrate that circular waste banks with formal recognition for waste pickers serve as the key mechanism for integrating informal actors. The study contributes a validated multi-dimensional theoretical framework for inclusive green economic well-being and provides evidence-based policy recommendations for medium-sized cities in developing countries.